PENGELOLAAN SUMBERDAYA PERIKANAN PELAGIS SECARA TERPADU DAN BERKELANJUTAN DI PERAIRAN TELUK TOMINI - Syahrul Syahrul (Indonesian Journal of Applied Sciences, 2012)
The purpose of this study were (1) recognize the potential and exploitation rate of pelagic fisheries resources, (2) analyze thesustainability status of pelagic fisheries resources, (3) examine the legal aspects of exploitation of pelagic fisheries resources (4) Develop the concept of integration in resource management of pelagic fisheries.The method used in this study include: (1)Surplus production models from Schaefer and Fox, (2) analysis for sustainability was using the Raps-Tomini and (3) study of the legal aspects (4) study of the integration of resource management of pelagic fisheries. The results showed that exploitation rate of pelagic fishery resources in the waters of Tomini Gulf still under fishing. Dimensions of ethics, law and regulations do not support the sustainability of pelagic fishery resources. Inadequate regulation in the integrated management in the Tomini Gulf. Required the establishment of an integrated regional management of pelagic fisheries resources in the waters Tomini Gulf.